(3JShjb GdNOeGJ (B:s (3eONd GSJQGJjLj hXjaj JWHjbj (B/s - (3GdWGFj, MejOs; (3GdYdGb, HTjQ s ((3YeGf(B: s (3OGQGdjGRhQj GdYdejI ddfTQ hGdJhRjY(B, s, 2009)
(3jVe eONd Gdi GdNOeGJ, GdNOeI GdLhgQ hGdNOeGJ GdJcejdjI GdOGYeI, GdeRjL GdJShjbj ddNOeGJ, OhQI MjGf GdefJL, JMOjO ecGfI GdNOeI aj GdJShjb, GfXeI GdNOeGJ, GdGSJQGJjLjGJ GdOGYeI dGfXeI GdNOeI, JUeje GdNOeI, GHJcGQ hJWhjQ GdNOeGJ GdLOjOI, EOGQI GdWdH Ydi GdNOeGJ, LhOI GdNOeI GdeOQcI hQVG GdeSJajO, JhRjY GdNOeGJ, JQhjL GdNOeGJ, GdJShjb GdOGNdj, GdeTcdGJ GdeJQJHI Ydi JShjb GdNOeGJs
(3GdeQGLY U(B.415s
Keywords: (3EOGQI GdCYeGds; (3GdJShjb(B- (3NOeGJs